„Ster” – pierwsze w Polsce radykalne czasopismo feministyczne przełomu XIX i XX wieku - Domarańczyk, Daria Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article tells the story of “Ster”, the first radical feminist magazine in Poland. It was first published in 1895–1896 in Lviv under the title “Ster. A magazine about the work and education of women”, and examined socio-cultural matters from the point of view of emancipated women. The editor-in-chief was Paulina Kuczalska-Reinschmit, and its writers included Eliza Orzeszkowa, Maria Konopnicka, Maria Dulębianka and Stefan Żeromski. After Kuczalska-Reinschmit moved to Warsaw, she reactivated the magazine as a bulletin for the Association of Emancipated Polish Women. It was then published from 1907 until the outbreak of World War I. The magazine presented the radical programme of Polish feminists. Among its later writers were P. Kuczalska-Reinschmit, Józefa Bojanowska and Romana Pachucka.